Ecologia da população de Pachystroma longifolium (Ness). I.M. Johnst. em área fragmentada de um remanescente de mata atlântica - Alcalá, Melina (Universidade Federal de São Carlos, 2010)
This study investigated the structure of spatial and ontogenetic stages of the species Pachystroma longifolium (Euphorbiaceae) in semideciduous forest in São Carlos, identifying and describing the post-germinative ontogenetic stages that characterize the development of the species, besides investigate whether the patterns allometric vary within and/or between ontogenetics stages. The spatial pattern was obtained using the aggregation index with the objective to check there are differences in spatial distribution pattern between ontogenetic stages and if these are determined by the preference of niches facilitators or arising from dispersion autochoric. In 1 ha were found 202 individuals and 4 ontogenetic stages were obtained: juvenile, immature, adult vegetative and reproductive adult. No seedlings were found in the plots and senile, which may be related to micro-environmental variation of the area or characteristics of the species. The branching pattern shown followed the Massart's architectural model, which is characteristic of species well adapted to low light conditions. All ontogenetic stages showed significant differences in height and diameter, indicating that they facing different environmental conditions and there is a great way allometric for each stage or group of stages, allowing for the best trade-off between stem diameter and height of plant. The population shows a patchy distribution, and the juveniles were those with the largest index of aggregation. Could not detect an effect of percentage of soil moisture on the distribution and density of individuals. As for the effect of percentage of canopy in the dry and rainy seasons, the correlation was positive and significant for the immature stage and the total of individuals in the area. The clustered pattern found for the population may be related both to autochoric dispersal strategies, as with the characteristics of the species.
Keywords: Ecologia vegetal; Ontogenia; Alometria; Distribuição espacial; Relação alométrica; Ontogeny; Allometry; Spatial pattern; CIENCIAS BIOLOGICAS::ECOLOGIA